Social influence & marketing: the Hush Puppies story - Kimmel, Allan J. (Henry Stewart Talks, 2016)
The case study uses the overnight comeback of the Hush Puppies shoe brand as an example of the powerful influence of word-of-mouth marketing on consumer behavior.